Delineating tesamorelin response pathways in HIV-associated NAFLD using a targeted proteomic and transcriptomic approach - Lindsay T. Fourman (Nature Portfolio, 2021)
Abstract NAFLD is a leading comorbidity in HIV with an exaggerated course compared to the general population. Tesamorelin has been demonstrated to reduce liver fat and prevent fibrosis progression in HIV-associated NAFLD. We further showed that tesamorelin downregulated hepatic gene sets involved in inflammation, tissue repair, and cell division. Nonetheless, effects of tesamorelin on individual plasma proteins pertaining to these pathways are not known. Leveraging our prior randomized-controlled trial and transcriptomic approach, we performed a focused assessment of 9 plasma proteins corresponding to top leading edge genes within differentially modulated gene sets. Tesamorelin led to significant reductions in vascular endothelial growth factor A (VEGFA, log2-fold change − 0.20 ± 0.35 vs. 0.05 ± 0.34, P = 0.02), transforming growth factor beta 1 (TGFB1, − 0.35 ± 0.56 vs. − 0.05 ± 0.43, P = 0.05), and macrophage colony stimulating factor 1 (CSF1, − 0.17 ± 0.21 vs. 0.02 ± 0.20, P = 0.004) versus placebo. Among tesamorelin-treated participants, reductions in plasma VEGFA (r = 0.62, P = 0.006) and CSF1 (r = 0.50, P = 0.04) correlated with a decline in NAFLD activity score. Decreases in TGFB1 (r = 0.61, P = 0.009) and CSF1 (r = 0.64, P = 0.006) were associated with reduced gene-level fibrosis score. Tesamorelin suppressed key angiogenic, fibrogenic, and pro-inflammatory mediators. CSF1, a regulator of monocyte recruitment and activation, may serve as an innovative therapeutic target for NAFLD in HIV. Clinical Trials Registry Number: NCT02196831